Breeding phenology and success of the Common Snipe Gallinago gallinago in the Azores. Issue 4 (2nd October 2019) - Rodrigues, Tiago M.; Rodrigues, Marisa; Gonçalves, David
ABSTRACT: Capsule: In comparison to other regions, the Common Snipe Gallinago gallinago in the Azores starts to display earlier and for a longer part of the year, but the laying period, although it starts earlier, does not seem to differ much from that observed elsewhere. Nesting success seems similar to that observed in other populations. Aims: This study aimed to infer the breeding phenology, characterize some basic breeding parameters, and quantify nesting success in a sedentary, and data deficient population of the Common Snipe. Methods: Counts of Common Snipe in display (2014) and searches of nests and broods (2011 and 2014) were conducted during the breeding season on São Jorge Island in the Azores. Additional data collected on São Miguel Island was also considered. Nests were monitored to assess nest survival. Results: The species was seen in display between January and August, and the laying period spanned between early March and late June. The probability of survival during the nesting period was 0.55 ( n  = 24; 95% – confidence limits: 0.38–0.80), and desertion was the main cause of failure. Conclusions: The best period to assess the population of Common Snipe in the Azores is during April, when the displaying activity is at its maximum. The species is very sensitive to disturbance during the nesting and rearing periods, thus managers should avoid interventions in the habitat between March and July to reduce disturbance.